Perovskite cell and preparation method and application thereof
By doping polar additives in perovskite batteries to form a modified perovskite layer, the problem of poor stability of perovskite batteries under extreme conditions is solved, and the high temperature resistance, aging resistance and extended service life of perovskite batteries are improved.
Patent Information
- Application Number
- CN202410578311.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-10
- Publication Date
- 2025-04-15
AI Technical Summary
Perovskite batteries have poor stability under extreme conditions such as light, moisture erosion, high temperature and high heat, resulting in a short service life.
The modified perovskite layer is formed by doping polar additives such as fluorine-containing resins, aluminum halides, chlorinated resins, etc. into the perovskite layer of the perovskite battery. The polar additive forms hydrogen bonds with the cations in the perovskite, forms coordination bonds with the excess Pb2+ ions, and improves the stability of the perovskite layer through its own cross-link and complexing ability.
The stability of the modified perovskite layer is significantly improved, and the high temperature and aging resistance of perovskite batteries are improved, and their service life is extended.
Smart Images

Figure CN119836107A_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present application relate to the technical field of solar cells, and in particular to a perovskite cell and a preparation method and application thereof. Background Art
[0002] Solar cells made of organic and inorganic halide perovskites have the advantages of high absorption coefficient, adjustable band gap, and simple preparation process, making single perovskite cells and stacked cells widely used in the photovoltaic field. However, perovskite cells still have inherent stability defects. Conventional perovskite materials have poor stability under conditions such as light, water erosion, high temperature and high heat, and the working environment of photovoltaic devices is difficult to avoid these intrusive factors. Therefore, it is urgent to provide a perovskite cell that still has good stability under extreme conditions. Summary of the invention
[0003] In view of this, the present application provides a perovskite battery and its preparation method and application. The perovskite battery obtains a modified perovskite layer by doping the perovskite lattice system with a polar additive. The polar additive can form a strong hydrogen bond with the cations in the perovskite, and can also bind to the excess Pb in the perovskite. 2+ The ions form coordination bonds. In addition, the polar additive molecules themselves also have strong cross-linking and bonding capabilities, which can effectively improve the stability of the perovskite functional phase and effectively slow down the decay of the perovskite functional phase into a mixed phase, thereby improving the overall stability of the modified perovskite layer, improving the high temperature resistance and aging resistance of the perovskite battery, and extending the service life of the battery.
[0004] In a first aspect, the present application provides a perovskite cell, wherein the perovskite cell comprises a modified perovskite layer, wherein the modified perovskite layer comprises perovskite and a polar additive, and at least a portion of the polar additive is doped in a crystal lattice of the perovskite.
[0005] In the embodiment of the present application, the polar additive includes any one of fluorine-containing resin, aluminum halide, chlorinated resin, polyethylene glycol or aniline.
[0006] In the embodiment of the present application, the fluorine-containing resin includes perfluoroethylene propylene copolymer or polyvinylidene fluoride; the aluminum halide includes AlF3 or AlCl3; the chlorinated resin includes polyvinylidene chloride, polychlorotrifluoroethylene or ethylenechlorotrifluoroethylene copolymer.
[0007] In the implementation manner of the present application, the mass percentage of the polar additive in the modified perovskite layer is 2‰-4‰.
[0008] In the embodiment of the present application, the thickness of the modified perovskite layer is 500nm-700nm.
[0009] In an embodiment of the present application, the perovskite cell further includes a conductive glass substrate stacked with the modified perovskite layer; and a hole transport layer disposed between the modified perovskite layer and the conductive glass substrate; and an electron transport layer and a negative electrode stacked in sequence on a surface of the modified perovskite layer away from the conductive glass substrate.
[0010] In the embodiment of the present application, the conductive glass substrate includes FTO conductive glass or ITO conductive glass;
[0011] The material of the hole transport layer includes one or more of NiO, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid, (4-(3,6-dimethyl-9H-carbazole-9-yl)butyl)phosphonic acid, and (2-(9H-carbazole-9-yl)ethyl)phosphonic acid;
[0012] The material of the electron transport layer includes fullerene, [6,6]-phenyl-C 61 - Any one of isomethyl butyrate and tin oxide;
[0013] The negative electrode includes a silver electrode or a copper electrode.
[0014] In the embodiment of the present application, the thickness of the conductive glass substrate is 1 mm-3 mm;
[0015] The thickness of the hole transport layer is 2nm-10nm;
[0016] The thickness of the electron transport layer is 20nm-35nm;
[0017] The thickness of the negative electrode is 90nm-200nm.
[0018] In the embodiment of the present application, the photoelectric conversion efficiency retention rate of the perovskite cell after aging for 1000 hours under the conditions of 85° C. and 85% relative humidity is greater than or equal to 90%.
[0019] The second aspect of the present application provides a method for preparing a perovskite battery, comprising:
[0020] Disposing a hole transport layer on the surface of the conductive glass substrate;
[0021] A perovskite precursor solution is prepared and coated on the surface of the hole transport layer, an anti-solvent containing a polar additive is added dropwise during the coating process, and an annealing treatment is performed after the coating is completed to obtain a modified perovskite layer;
[0022] An electron transport layer and a negative electrode are sequentially formed on the surface of the modified perovskite layer to obtain a perovskite battery.
[0023] In an embodiment of the present application, the anti-solvent includes a first component and a second component; the first component includes isopropanol; and the second component includes any one of ethyl acetate, chlorobenzene and anisole.
[0024] In the embodiment of the present application, the volume of the first component accounts for 2%-10% of the total volume of the first component and the second component.
[0025] In the embodiment of the present application, the concentration of the polar additive in the anti-solvent is 0.1 mg / mL-2 mg / mL; the dripping speed is 50 μL / s-200 μL / s.
[0026] In the embodiment of the present application, the heating rate of the annealing treatment is 10°C / s-20°C / s; the holding temperature is 100°C-120°C; and the holding time is 10min-30min.
[0027] A third aspect of the present application provides a photovoltaic system, which includes the perovskite cell provided in the first aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 A schematic diagram of the cross-sectional structure of a perovskite battery provided in one embodiment of the present application;
[0029] Figure 2 A flowchart of a method for preparing a perovskite battery provided in one embodiment of the present application;
[0030] Figure 3 This is an EDS analysis (Energy-Dispersive X-ray Spectroscopy) spectrum of the modified perovskite layer prepared in Example 1 of the present application;
[0031] Figure 4 This is the EDS analysis spectrum of the perovskite layer prepared in Comparative Example 1 of the present application;
[0032] Figure 5 This is a SEM (Scanning Electron Microscope) characterization image of the modified perovskite layer prepared in Example 1 of the present application;
[0033] Figure 6 This is a SEM characterization image of the perovskite layer prepared in Comparative Example 1 of the present application.
[0034] Description of Figure Numbers
[0035] 100 - perovskite cell; 101 - conductive glass substrate; 102 - hole transport layer; 103 - modified perovskite layer; 104 - electron transport layer; 105 - interface modification layer; 106 - negative electrode; 107 - encapsulation layer. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0037] Solar cells made of organic and inorganic halide perovskites have the advantages of high absorption coefficient, adjustable band gap, and simple preparation process, making single-cell perovskite cells and stacked cells widely used in the photovoltaic field. However, perovskite cells still have inherent stability defects: the light absorption and conversion ability of the perovskite layer is weakened due to the defects of the perovskite layer itself, the increase of impurity phases, ion migration, and lattice distortion of the perovskite; the metal of the electrode layer reacts with the perovskite layer under the action of ion migration, resulting in corrosion of the perovskite layer and the electrode layer; the hole transport layer such as NiO has a certain reducibility and will react with the cations in the perovskite layer. The above reasons lead to the poor stability of conventional perovskite materials under conditions such as light, water erosion, high temperature and high heat, and it is difficult for the working environment of photovoltaic devices to avoid these intrusive factors.
[0038] At present, the ways to improve the stability of perovskite batteries include: adding a crosslinking agent directly to the perovskite precursor solution; inserting a passivation agent layer between the perovskite layer and the electron transport layer, etc. However, if the crosslinking agent is directly dissolved in the perovskite precursor solution, the perovskite precursor solution will gel before spin coating, making it impossible to spin coat the solution, and thus unable to complete the battery preparation; and inserting a passivation agent layer between the perovskite layer and the electron transport layer can only improve the stability of the perovskite at the interface between the perovskite layer and the electron transport layer, and cannot improve the overall stability of the perovskite layer with a thickness of several hundred nanometers.
[0039] In view of the above problems, the present application provides a perovskite battery and its preparation method and application. The perovskite battery obtains a modified perovskite layer by doping the perovskite lattice system with a polar additive. The polar additive can form a strong hydrogen bond with the cations in the perovskite, and can also bind to the excess Pb in the perovskite. 2+ The ions form coordination bonds. In addition, the polar additive molecules themselves also have strong cross-linking and bonding capabilities, which can effectively improve the stability of the perovskite functional phase and effectively slow down the decay of the perovskite functional phase into a mixed phase, thereby improving the overall stability of the modified perovskite layer, improving the high temperature resistance and aging resistance of the perovskite battery, and extending the service life of the battery.
[0040] The embodiment of the present application provides a perovskite battery, including a modified perovskite layer, the modified perovskite layer including perovskite and a polar additive, wherein at least part of the polar additive is doped in the lattice of the perovskite. In the embodiment of the present application, in the modified perovskite layer, part of the polar additive may be doped in the lattice of the perovskite; or all of the polar additive may be doped in the lattice of the perovskite. The polar additive of the present application has a strong polarity, and when it is introduced into the lattice structure of the perovskite layer, on the one hand, the polar additive can form a strong hydrogen bond with the cations in the perovskite, and has a strong binding force, which effectively prevents the cations in the perovskite layer from reacting with the materials in the reducing hole transport layer in the battery, and prevents the phase segregation caused by the diffusion and migration of cations, so that the functional phase α phase obtains a longer life, thereby improving the stability of the perovskite battery; on the other hand, the polar additive can also react with the excess lead iodide or Pb in the perovskite. 2+ ions form coordination bonds, effectively preventing I - The ions react with the negative electrode under the action of migration, effectively delaying the corrosion of the electrode material on the perovskite layer. In addition, due to the strong polarity of the polar additives themselves, the polar additive molecules themselves also have strong cross-linking and bonding ability. This complexing ability can effectively improve the stability of the functional phase α phase crystal that can produce photoelectric energy conversion in the perovskite. At the same time, it can also effectively alleviate the degradation of the functional phase α phase into useless impurity phase β phase, γ phase and decomposition products such as lead iodide, thereby reducing the generation of impurities and improving the photoelectric conversion efficiency and stability of the perovskite layer.
[0041] In some embodiments of the present application, the polar additive includes any one of a fluorine-containing resin, an aluminum halide, a chlorinated resin, polyethylene glycol or an aniline. In some embodiments of the present application, the fluorine-containing resin includes a perfluoroethylene propylene copolymer (FEP) or a polyvinylidene fluoride (PVDF); the aluminum halide includes AlF3 or AlCl3; the chlorinated resin includes polyvinylidene chloride (PVDC), polytrifluorochloroethylene (PCTFE) or ethylene trifluorochloroethylene copolymer (ECTFE). The present application further improves the high temperature resistance and aging resistance of the perovskite battery by selecting suitable anions with strong polarity, capable of producing hydrogen bonds or having strong non-metallic properties as polar additives to dope the perovskite lattice system, thereby broadening the application scenarios of the perovskite battery and extending the service life of the perovskite battery. In some specific embodiments of the present application, the polar additive may be, for example, FEP. FEB, as a fluorine-containing resin with strong polarity, also has the characteristics of low price and simple and easy-to-obtain raw materials. The selection of FEB as a polar additive can effectively improve the stability of the modified perovskite layer while effectively reducing the production cost.
[0042] In the implementation manner of the present application, the mass percentage of the polar additive in the modified perovskite layer is 2‰-4‰. The present application controls the amount of polar additive added in the modified perovskite layer within a suitable range, thereby further improving the stability of the battery while ensuring the battery capacity and cost. In some specific implementation manners of the present application, the mass percentage of the polar additive in the modified perovskite layer can be, for example, 2‰, 2.5‰, 3‰, 3.5‰, 4‰.
[0043] In the embodiment of the present application, the thickness of the modified perovskite layer is 500nm-700nm. Controlling the thickness of the modified perovskite layer within the above range can ensure the photoelectric conversion efficiency of the perovskite layer while making its thickness adapt to the bending and folding requirements of the perovskite battery. In the embodiment of the present application, the thickness of the modified perovskite layer can be, for example, 500nm, 550nm, 600nm, 650nm, 700nm.
[0044] In the embodiment of the present application, the perovskite cell further comprises a conductive glass substrate laminated with the modified perovskite layer provided above; and a hole transport layer disposed between the modified perovskite layer and the conductive glass substrate; and an electron transport layer and a negative electrode laminated sequentially on the surface of the modified perovskite layer away from the conductive glass substrate. In some specific embodiments of the present application, the perovskite cell further comprises an interface modification layer and an encapsulation layer. Figure 1 As shown, the perovskite cell 100 includes a conductive glass substrate 101, a hole transport layer 102, a modified perovskite layer 103, an electron transport layer 104, an interface modification layer 105, a negative electrode 106 and an encapsulation layer 107 which are stacked in sequence.
[0045] In the embodiment of the present application, the conductive glass substrate includes FTO (F-doped Tin Oxide) conductive glass or ITO conductive glass. In some specific embodiments of the present application, the conductive glass is FTO conductive glass, which is fluorine-doped tin dioxide conductive glass. FTO conductive glass has high transparency and conductivity, and the cost is relatively low. Compared with ITO (Indium Tin Oxides) conductive glass, FTO conductive glass has better heat resistance. Its application in perovskite batteries can further improve its stability and aging resistance under high temperature conditions, thereby further improving the service life of the battery. In the embodiment of the present application, the thickness of the conductive glass substrate is 1mm-3mm. Controlling the thickness of the conductive glass within the above-mentioned appropriate range can make it have good conductivity and good optical properties. In some specific embodiments, the thickness of the conductive glass substrate can be, for example, 1mm, 1.5mm, 2mm, 2.5mm, 3mm.
[0046] In the embodiment of the present application, the material of the hole transport layer includes one or more of NiO, poly [bis (4-phenyl) (2,4,6-trimethylphenyl) amine] (PTAA), (2- (3,6-dimethoxy-9H-carbazole-9-yl) ethyl) phosphonic acid (MeO-2PACz), (4- (3,6-dimethyl-9H-carbazole-9-yl) butyl) phosphonic acid (Me-4PACz) and (2- (9H-carbazole-9-yl) ethyl) phosphonic acid (2PACz). Selecting a hole transport layer of suitable material can provide more hole transport channels, improve hole transport efficiency, and improve photoelectric conversion efficiency. In some embodiments of the present application, the hole transport layer includes a first hole transport layer and a second hole transport layer. The material of the first hole transport layer may be, for example, NiO or PTAA, and the material of the second hole transport layer may be, for example, a self-assembled monolayer (SAM) material, specifically (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid (MeO-2PACz), (4-(3,6-dimethyl-9H-carbazole-9-yl)butyl)phosphonic acid (Me-4PACz) and (2-(9H-carbazole-9-yl)ethyl)phosphonic acid (2PACz). In an embodiment of the present application, the thickness of the hole transport layer is 2nm-10nm. In some specific embodiments, the thickness of the hole transport layer may be, for example, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm. Controlling the thickness of the hole transport layer within an appropriate range can further improve the hole transport efficiency of the hole transport layer. In some embodiments of the present application, the material of the first hole transport layer is NiO. NiO is inexpensive and the preparation process of the hole transport layer using it is simple. It is stable and reliable after preparation and also helps to improve the interface wettability between the hole transport layer and the modified perovskite layer. Spin coating the SAM material as the second hole transport layer on the first hole transport layer can adjust the energy band of the overall hole transport layer, so that the energy levels between the hole transport layer and the modified perovskite layer are more matched, and can also further improve the open circuit voltage and current of the battery.
[0047] In the embodiment of the present application, the material of the electron transport layer includes fullerene, [6,6]-phenyl-C 61 - any one of isomethyl butyrate and tin oxide. The electron transport layer can provide more electron transport channels and improve the electron transport efficiency. In some specific embodiments of the present application, the material of the electron transport layer includes C 60In an embodiment of the present application, the thickness of the electron transport layer is 20nm-35nm. In some specific embodiments of the present application, the thickness of the electron transport layer can be, for example, 20nm, 22nm, 24nm, 25nm, 26nm, 28nm, 30nm, 32nm, 34nm, 35nm. Controlling the thickness of the electron transport layer within a suitable thickness range can further improve the electron transport efficiency of the electron transport layer.
[0048] In some embodiments of the present application, the perovskite battery also includes an interface modification layer. In some specific embodiments, the material of the interface modification layer includes one or more of 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP), lithium fluoride (LiF), magnesium fluoride (LiMg), aluminum oxide (Al2O3) and phenylethylamine iodine (PEAI). By selecting a suitable material as the interface modification layer of the battery, the carrier mobility can be effectively improved, electrons can be transmitted, holes can be blocked, and the photovoltaic performance of the perovskite battery can be better improved. In some specific embodiments of the present application, the material of the interface modification layer includes 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP). In the embodiment of the present application, the thickness of the interface modification layer is 2mm-5mm. Controlling the thickness of the interface modification layer within a suitable range can further improve the photovoltaic performance of the battery. In some specific embodiments of the present application, the thickness of the interface modification layer can be, for example, 2mm, 2.5mm, 3mm, 3.5mm, 4mm, 4.5mm, 5mm.
[0049] In an embodiment of the present application, the negative electrode includes a silver electrode or a copper electrode. In some specific embodiments of the present application, the negative electrode is a silver electrode. In an embodiment of the present application, the thickness of the negative electrode is 90nm-200nm. In some specific embodiments of the present application, the thickness of the negative electrode can be, for example, 90nm, 100nm, 110nm, 120nm, 130nm, 150nm, 160nm, 180nm, 200nm. The present application can further improve the interfacial electron transmission efficiency, reduce energy loss, and thereby improve the photoelectric conversion efficiency and stability of the battery by selecting a suitable negative electrode material and controlling its thickness within a suitable range.
[0050] In an embodiment of the present application, the encapsulation layer includes an encapsulation film and an encapsulation glass arranged in a stacked manner. In some specific embodiments, the encapsulation film may be, for example, polyisobutylene, polyolefin, polyurethane, polyethylene octene co-elastomer (POE), etc. In an embodiment of the present application, the thickness of the encapsulation layer is 1mm-2mm. In some specific embodiments of the present application, the thickness of the encapsulation layer may be, for example, 1mm, 1.1mm, 1.2mm, 1.3mm, 1.4mm, 1.5mm, 1.6mm, 1.7mm, 1.8mm, 1.9mm, 2mm. The thickness of the encapsulation layer is controlled within a suitable range to effectively protect the electrodes and various functional layers of the perovskite battery while ensuring good optical properties.
[0051] In the embodiment of the present application, the efficiency retention rate of the perovskite battery after aging for 1000 hours at 85°C and 85% relative humidity is greater than or equal to 90%. In some specific embodiments of the present application, the efficiency retention rate of the perovskite battery after aging for 1000 hours at 85°C and 85% relative humidity can be, for example, 90%, 92%, 93%, 94%, 95%, 96%, 97%, 98%. The perovskite battery provided in the present application obtains a modified perovskite layer by doping the perovskite lattice system with a polar additive, which effectively improves the overall stability of the modified perovskite layer, thereby improving the high temperature resistance and aging resistance of the perovskite battery and extending the service life of the battery.
[0052] This application also provides a method for preparing a perovskite battery, the specific process is as follows Figure 2 As shown, including:
[0053] S101, providing a hole transport layer on the surface of a conductive glass substrate;
[0054] S102, preparing a perovskite precursor solution and coating it on the surface of the hole transport layer, adding dropwise an anti-solvent containing a polar additive during the coating process, and performing an annealing treatment after the coating to obtain a modified perovskite layer;
[0055] S103, sequentially forming an electron transport layer and a negative electrode on the surface of the modified perovskite layer; and obtaining a perovskite battery.
[0056] In step S102, the coating method includes but is not limited to the coating methods commonly used in the fields of spin coating and scraping. In some embodiments of the present application, the coating method may be, for example, spin coating. In some embodiments, the spin coating speed is 1000rpm-4000rpm; the spin coating time is 30s-60s. In some specific embodiments of the present application, spin coating can be performed in two steps. The first step is to spin coat at a speed of 1000rpm for 10s, and the second step is to spin coat at a speed of 4000rpm for 35s. After a uniform and stable perovskite wet film is formed at the 30th second of spin coating, that is, at the 20th second of the second step of spin coating, an anti-solvent containing a polar additive is added dropwise, and the spin coating is continued for 15s before annealing.
[0057] In the embodiment of the present application, the anti-solvent includes a first component and a second component, wherein the first component includes isopropanol; the second component includes one or more of ethyl acetate, chlorobenzene and anisole. Since the polar additive has a strong polarity, when it is directly dissolved in the perovskite precursor, the polar additive will be complexed with cations such as methylamine and methyl imidazole, thereby causing the perovskite precursor solution to condense and agglomerate, causing the perovskite precursor solution to be unable to form a uniform and complete perovskite film when coated on the surface of the hole transport layer. Therefore, the present application controls the solubility of the polar additive by dissolving the polar additive in an anti-solvent suitable for the component, and drips the anti-solvent dissolved with the polar additive during the coating process of the perovskite precursor solution, and annealing treatment is performed to precipitate the supersaturated crystals, on the one hand, the polar additive is introduced to improve the stability of the perovskite layer, and on the other hand, the thickness uniformity and integrity of the perovskite layer are also guaranteed. Among them, the isopropanol in the first component can improve the solubility of the anti-solvent for polar additives, and the second component plays an extraction role for perovskite, so that the perovskite in the perovskite wet film obtained after coating is in an oversaturated state, and can be quickly crystallized to form a perovskite layer after subsequent annealing. In some specific embodiments of the present application, the anti-solvent is isopropanol and ethyl acetate in a volume ratio of 5:95. Since some polar additives are difficult to dissolve in some anti-solvent solutions, adding a small amount of isopropanol to the anti-solvent can further promote the dissolution of polar additives.
[0058] In the implementation mode of the present application, the volume of the first component accounts for 2%-10% of the total volume of the first component and the second component. Controlling the ratio of the two within a suitable range can make the polar additive have a suitable solubility in the anti-solvent, while ensuring that the anti-solvent has a suitable solubility for the polar additive, and improving the extraction effect of the anti-solvent on the perovskite. The perovskite in the perovskite wet film obtained after coating is in an oversaturated state, and can be quickly crystallized to form a perovskite layer after subsequent annealing. In some specific embodiments of the present application, the volume of the first component can, for example, account for 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% of the total volume of the first component and the second component.
[0059] In an embodiment of the present application, the concentration of the polar additive in the antisolvent is 0.1mg / mL-2mg / mL. In some specific embodiments of the present application, the concentration of the polar additive in the antisolvent can be, for example, 0.1mg / mL, 0.2mg / mL, 0.3mg / mL, 0.4mg / mL, 0.5mg / mL, 0.6mg / mL, 0.8mg / mL, 1mg / mL, 1.2mg / mL, 1.5mg / mL, 1.8mg / mL. In an embodiment of the present application, the dripping speed is 50μL / s-200μL / s. In some specific embodiments of the present application, the dripping speed can be, for example, 50μL / s, 60μL / s, 70μL / s, 80μL / s, 90μL / s, 100μL / s, 150μL / s, 200μL / s. Controlling the concentration of the polar additive in the antisolvent and the rate of dripping within a suitable range can control the reaction rate of the polar additive with the perovskite precursor, thereby effectively avoiding agglomeration or condensation due to excessive reaction speed of the two, and can also control the doping amount of the polar additive in the modified perovskite precursor.
[0060] In the implementation manner of the present application, the heating rate of the annealing treatment is 10°C / s-20°C / s; the holding temperature is 100°C-120°C; and the holding time is 10min-30min. In some specific implementation manners of the present application, the heating rate of the annealing treatment can be, for example, 10°C / s, 11°C / s, 12°C / s, 13°C / s, 14°C / s, 15°C / s, 16°C / s, 17°C / s, 18°C / s, 19°C / s, 20°C / s; the holding temperature can be, for example, 100°C, 105°C, 110°C, 115°C, 120°C; and the holding time can be, for example, 10min, 15min, 20min, 25min, 30min. The annealing treatment can cause the spin-coated thick perovskite wet film in an oversaturated state to be heated and crystallized to form a functional phase α phase with photoelectric conversion capability. The formula components of the perovskite layer change, and the corresponding energy band gap will also change accordingly. The larger the band gap, the lower the required annealing temperature and the shorter the insulation time; the smaller the band gap, the higher the required annealing temperature and the longer the insulation time. Therefore, the annealing parameters can be adjusted according to the actual needs of the perovskite layer with different formula components. Controlling the annealing parameters within an appropriate range can ensure that the supersaturated perovskite wet film is fully and evenly formed into α-phase crystals after heating, and can also effectively avoid the occurrence of cracking, perforation, halide segregation and other phenomena caused by excessively high temperatures in the perovskite layer. In one embodiment of the present application, the component of the perovskite layer is Cs 0.05 (Fa 0.79 Ma 0.21 ) 0.95 Pb(I 0.79 Br0.21 )3. At this time, the holding temperature of the annealing treatment is 100°C and the holding time is 20 minutes.
[0061] The preparation method of the perovskite battery provided in the present application extracts the perovskite wet film by introducing a polar additive into an anti-solvent, thereby obtaining a uniform and stable modified perovskite layer and at the same time incorporating the polar additive into the lattice system of the perovskite, thereby obtaining a highly stable perovskite material.
[0062] The embodiment of the present application also provides a photovoltaic system, which includes the perovskite cell provided in the foregoing text of the present application. The photovoltaic system improves the high temperature resistance and aging resistance of the photovoltaic system through the perovskite cell with a modified perovskite layer.
[0063] The present application is further described below in multiple embodiments:
[0064] Example 1
[0065] Weigh 33.5 mg of MABr, 19.5 mg of CsI, 542.5 mg of PbI2, 193.6 mg of FAI, and 118.5 mg of PbBr2 and dissolve them in a mixed solvent of 200 μL of dimethyl sulfoxide (DMSO) and 800 μL of N,N-dimethylformamide (DMF) to obtain a Cs solution with a concentration of 1.5 mol / mL. 0.05 (FA 0.79 MA 0.21 ) 0.95 Pb(I 0.79 Br 0.21 )3Perovskite precursor solution;
[0066] Dissolving 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP) in isopropanol solvent to obtain a surface modification layer precursor solution with a concentration of 0.5 mg / mL;
[0067] Dissolve (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid (MeO-2PACz) in anhydrous ethanol to obtain a second hole transport layer precursor solution with a concentration of 0.5 mg / mL;
[0068] Dissolving nickel oxide in deionized water to obtain a first hole transport layer precursor solution with a concentration of 8 mg / mL;
[0069] Dissolving fluorinated ethylene propylene (FEP) in a mixed solvent of 95% by volume ethyl acetate and 5% by volume isopropanol to obtain an anti-solvent containing FEP at a concentration of 0.5 mg / mL;
[0070] Use FTO as a conductive glass substrate, scrub it before use, and then use a detergent, deionized water, and anhydrous ethanol for 10 minutes of ultrasound. Blow dry with nitrogen for use; use a plasma cleaner to treat the FTO conductive glass substrate after cleaning for 8 minutes; spin-coat 8mg / ml NiO first hole transport layer precursor solution at a speed of 4000rpm to obtain the first hole transport layer, and then spin-coat 0.5mg / ml MEO-2PACz second hole transport layer precursor solution at a speed of 6000rpm to obtain the second hole transport layer; spin-coat the perovskite precursor solution at a speed of 4000rpm for 45s, and add 0.5mg / ml FEP (95% ethyl acetate and 5% isopropanol mixed solvent) anti-solvent at a speed of 60μL / s 15s before the end of spin coating. After the spin coating, anneal at 100℃ for 20min to obtain a modified perovskite layer; vacuum evaporate 30nm thick fullerene (C 60 ) to obtain an electron transport layer; spin coating with 0.5 mg / ml BCP (bathocuproine) solution at 4000 rpm for 30 s to obtain a surface modification layer; vacuum evaporation of 100 nm thick silver electrode; after the preparation of a single battery, a circle of packaging materials such as polyisobutylene, polyurethane, POE, etc. is attached to the edge of the battery, and then hot-pressed at 80 kPa and 95 ° C for 300 s to complete the battery packaging and obtain a perovskite battery.
[0071] Example 2
[0072] The difference from Example 1 is that the anti-solvent is a mixed solvent of 95% by volume chlorobenzene and 5% by volume isopropanol.
[0073] Example 3
[0074] The difference from Example 1 is that the concentration of FEP in the anti-solvent is 0.1 mg / mL.
[0075] Example 4
[0076] The difference from Example 1 is that the concentration of FEP in the anti-solvent is 2 mg / mL.
[0077] Example 5
[0078] The difference from Example 1 is that the dropping speed of the anti-solvent containing FEP is 200 μL / s.
[0079] Example 6
[0080] The difference from Example 1 is that the annealing temperature is 120°C.
[0081] Example 7
[0082] The difference from Example 1 is that FEP is replaced by polyvinylidene fluoride (PVDF).
[0083] Comparative Example 1
[0084] The difference from Example 1 is that no polar additive is added.
[0085] Comparative Example 2
[0086] Weigh 33.5 mg of MABr, 19.5 mg of CsI, 542.5 mg of PbI2, 193.6 mg of FAI, and 118.5 mg of PbBr2 and dissolve them in a mixed solvent of 200 μL of dimethyl sulfoxide (DMSO) and 800 μL of N,N-dimethylformamide (DMF) to obtain a Cs solution with a concentration of 1.5 mol / mL. 0.05 (FA 0.79 MA 0.21 ) 0.95 Pb(I 0.79 Br 0.21 )3Perovskite precursor solution;
[0087] Dissolving 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP) in isopropanol solvent to obtain a surface modification layer precursor solution with a concentration of 0.5 mg / mL;
[0088] Dissolve (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid (MeO-2PACz) in anhydrous ethanol to obtain a second hole transport layer precursor solution with a concentration of 0.5 mg / mL;
[0089] Dissolving nickel oxide in deionized water to obtain a first hole transport layer precursor solution with a concentration of 8 mg / mL;
[0090] Dissolving fluorinated ethylene propylene (FEP) in a mixed solvent of 95% by volume ethyl acetate and 5% by volume isopropanol to obtain an anti-solvent containing FEP at a concentration of 0.5 mg / mL;
[0091] FTO was used as a conductive glass substrate, which was scrubbed before use, and then ultrasonically treated with a detergent, deionized water, and anhydrous ethanol for 10 minutes respectively. The substrate was dried with nitrogen and set aside for use; the FTO conductive glass substrate after cleaning was treated with a plasma cleaner for 8 minutes; 8 mg / ml NiO first hole transport layer precursor solution was spin-coated at a speed of 4000 rpm to obtain the first hole transport layer, and then 0.5 mg / ml MEO-2PACz second hole transport layer precursor solution was spin-coated at a speed of 6000 rpm to obtain the second hole transport layer; an anti-solvent (95% ethyl acetate and 5% isopropanol mixed solvent) containing 0.5 mg / ml FEP was added to the perovskite precursor solution for spin coating, and annealed at 100°C for 20 minutes after the spin coating was completed. Due to the agglomeration and condensation of the slurry, the modified perovskite layer could not be obtained, and the perovskite battery could not be obtained.
[0092] The modified perovskite layer prepared in Example 1 and the perovskite layer prepared in Comparative Example 1 were subjected to EDS analysis (Energy-Dispersive X-ray Spectroscopy, X-ray energy spectrum analysis), and the results obtained were as follows: Figure 3 and Figure 4 shown. Figure 3 This is the EDS analysis spectrum of the modified perovskite layer prepared in Example 1. By calibrating the elements F, Pb, and I, it can be seen that in Example 1 of the present application, the perovskite layer is modified by using a polar additive fluorinated ethylene propylene (FEP). The distribution area of the F element is consistent with the contour of the modified perovskite layer area, and is almost completely consistent with the distribution trend of the perovskite-specific elements Pb and I, indicating that at least part of the polar additive FEP is doped in the perovskite lattice. Figure 4 It can be seen from the EDS analysis spectrum of (Comparative Example 1) that the detection of the F element in the perovskite layer without adding polar additives is blank, with only background response.
[0093] The modified perovskite layer obtained in Example 1 and the perovskite layer obtained in Comparative Example 1 were characterized by SEM (Scanning Electron Microscope), and the results obtained were as follows: Figure 5 and Figure 6 As shown. Figure 5 (Example 1) and Figure 6(Comparative Example 1) It can be seen that after the perovskite layer is modified by adding polar additives in Example 1 of the present application, the perovskite grains are significantly larger and the grain boundaries are clearer. This is because the fluorine-containing resin FEP forms a certain complexing ability with the perovskite precursor by forming coordination bonds and hydrogen bonds, becoming a nucleation site, which promotes the formation of large grains with clear interfaces during the crystallization of perovskite. Therefore, the surface morphology characterization by SEM can also assist EDS as an indirect proof that the polar additive enters the perovskite lattice during the spin coating process.
[0094] Aging resistance test:
[0095] The perovskite cells prepared in the embodiments and comparative examples were subjected to stability tests. The test method was as follows: after packaging, the perovskite cells were placed in a device at a temperature of 85°C and a relative humidity of 85% for continuous heating, and photoelectric conversion efficiency tests were performed regularly. After the test, heat aging was continued. The ratio of the conversion efficiency after 1000 hours of heat aging to the conversion efficiency before aging was the retention rate after aging. The measured results are shown in Table 1.
[0096] Table 1 Aging resistance test results
[0097]
[0098]
[0099] It can be seen from the data in Table 1 that, compared with Comparative Example 1 in which no polar additive is added, the present application can significantly improve the photoelectric conversion efficiency preservation rate of the perovskite battery after aging for 1000 hours by doping the polar additive into the perovskite lattice system in the embodiment, thereby improving its stability under high temperature conditions. In addition, in Comparative Example 2, the polar additive is directly added to the perovskite precursor solution, which causes it to agglomerate and condense, and it is impossible to spin-coat to obtain a modified perovskite layer, and thus it is impossible to obtain a perovskite battery.
[0100] The above is an exemplary embodiment of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made thereto without departing from the principles of the present application. These improvements and modifications are also considered to be within the scope of protection of the present application.
Claims
1. A perovskite battery, characterized in that: The perovskite cell comprises a modified perovskite layer, wherein the modified perovskite layer comprises perovskite and a polar additive, and at least a portion of the polar additive is doped in a crystal lattice of the perovskite.
2. The perovskite battery according to claim 1, characterized in that The polar additive includes any one of fluorine-containing resin, aluminum halide, chlorinated resin, polyethylene glycol or aniline; the fluorine-containing resin includes perfluoroethylene propylene copolymer or polyvinylidene fluoride; the aluminum halide includes AlF3 or AlCl3; the chlorinated resin includes polyvinylidene chloride, polychlorotrifluoroethylene or ethylenechlorotrifluoroethylene copolymer.
3. The perovskite battery according to claim 1 or 2, characterized in that: The mass percentage of the polar additive in the modified perovskite layer is 2‰-4‰.
4. The perovskite battery according to any one of claims 1 to 3, characterized in that: The thickness of the modified perovskite layer is 500nm-700nm.
5. The perovskite battery according to any one of claims 1 to 4, characterized in that: It also includes a conductive glass substrate stacked with the modified perovskite layer; a hole transport layer arranged between the modified perovskite layer and the conductive glass substrate; and an electron transport layer and a negative electrode stacked in sequence on the surface of the modified perovskite layer away from the conductive glass substrate.
6. The perovskite battery according to claim 5, characterized in that: The conductive glass substrate comprises FTO conductive glass or ITO conductive glass; The material of the hole transport layer includes one or more of NiO, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid, (4-(3,6-dimethyl-9H-carbazole-9-yl)butyl)phosphonic acid, and (2-(9H-carbazole-9-yl)ethyl)phosphonic acid; The material of the electron transport layer includes fullerene, [6,6]-phenyl-C 61 - Any one of isomethyl butyrate and tin oxide; The negative electrode includes a silver electrode or a copper electrode.
7. The perovskite battery according to claim 5 or 6, characterized in that: The thickness of the conductive glass substrate is 1 mm to 3 mm; The thickness of the hole transport layer is 2nm-10nm; The thickness of the electron transport layer is 20nm-35nm; The thickness of the negative electrode is 90nm-200nm.
8. The perovskite battery according to any one of claims 1 to 7, characterized in that: The photoelectric conversion efficiency retention rate of the perovskite cell after aging for 1000 hours under the conditions of 85° C. and 85% relative humidity is greater than or equal to 90%.
9. A method for preparing a perovskite battery, characterized in that: include: Disposing a hole transport layer on the surface of the conductive glass substrate; A perovskite precursor solution is prepared and coated on the surface of the hole transport layer, an anti-solvent containing a polar additive is added dropwise during the coating process, and an annealing treatment is performed after the coating is completed to obtain a modified perovskite layer; An electron transport layer and a negative electrode are sequentially formed on the surface of the modified perovskite layer to obtain a perovskite battery.
10. The method for preparing a perovskite battery according to claim 9, characterized in that: The anti-solvent comprises a first component and a second component; the first component comprises isopropanol; the second component comprises any one of ethyl acetate, chlorobenzene and anisole; and the volume of the first component accounts for 2%-10% of the total volume of the first component and the second component.
11. The method for preparing a perovskite battery according to claim 9 or 10, characterized in that: The concentration of the polar additive in the anti-solvent is 0.1 mg / mL-2 mg / mL; the dropping speed is 50 μL / s-200 μL / s.
12. The method for preparing a perovskite battery according to any one of claims 9 to 11, characterized in that: The heating rate of the annealing treatment is 10°C / s-20°C / s; the insulation temperature is 100°C-120°C; and the insulation time is 10min-30min.
13. A photovoltaic system, characterized in that: The photovoltaic system comprises the perovskite cell according to any one of claims 1 to 8 or the perovskite cell prepared by the preparation method according to any one of claims 9 to 12.